Sweet liker status in children and adults: Consequences for beverage intake in adults. (April 2018) - Garneau, Nicole L.; Nuessle, Tiffany M.; Mendelsberg, Barbara J.; Shepard, Stephanie; Tucker, Robin M.
Highlights: Liking patterns for adults included "likers", "dislikers", and "neutrals". Liking patterns for children included "likers" and "dislikers". No differences in sex, age, BMI, or BMI z-score were observed between the groups. In children and adults, liking scores across concentrations differed by cluster. Adult sweet likers consumed more total energy from beverages than neutral raters. Abstract: Different patterns of sweet liking exist. For some, liking increases as concentration increases up to a point at which it typically plateaus. These individuals are referred to as sweet likers. How sweet likers' beverage intake, especially sugar sweetened beverage intake, differs from sweet dislikers' beverage intake is not well characterized. A total of 953 visitors (650 adults; 62.0% women; 303 children; 58.7% girls) to the Denver Museum of Nature & Science rated the taste intensity and liking of 5 sucrose solutions that spanned concentrations typically encountered in sugar-sweetened beverages (0.0–13.7% w/v) using visual analog scales. Beverage intake by adults was quantified using the validated BEVQ-15 questionnaire. Among adults, hierarchical cluster analysis identified three clusters of liking patterns (likers, dislikers, and neutrals). Among children, two clusters of liking patterns were identified (likers and dislikers). For both adults and children, BMI, percent body fat, age, and sex did not differ between clusters. Concentration by cluster interaction effects were observed for both adults and children. Adult sweet likers consumed more energy from all beverages, more sweetened juice and tea, and less water than those in other clusters. Sweet liker status may be a useful predictor of increased energy intake from beverages, but prospective trials are necessary to confirm this utility.